Spatial Planning Policy in Overcoming Urban Sprawl in Makassar City - Asmansyah Asmansyah; A. Hadijah Sulfiyani A (ASHA Publishing, 2026)
Urban sprawl has become one of the major spatial challenges faced by Makassar City amid rapid urban growth and suburban expansion. The increasing conversion of agricultural and open land into residential, commercial, and infrastructure areas has encouraged uncontrolled urban expansion toward peri urban areas such as Biringkanaya, Tamalanrea, and surrounding corridors. This condition has created various urban problems including traffic congestion, inefficient infrastructure services, environmental degradation, flood vulnerability, and fragmented land use patterns. This study aims to analyze the role of spatial planning policies in addressing urban sprawl in Makassar City and to identify the main challenges in controlling spatial expansion in suburban areas. The research uses a qualitative approach through library research by examining various scientific studies related to urban sprawl, land use change, suburban development, and spatial planning policies in Makassar. Data were analyzed descriptively and critically to understand the relationship between urban expansion and the effectiveness of spatial planning policies. The findings indicate that urban sprawl in Makassar is driven not only by population growth and urbanization, but also by weak spatial control, increasing real estate development, transportation accessibility, and uneven urban development patterns. Existing spatial planning policies have not fully controlled dispersed urban growth, particularly in peri urban areas experiencing rapid land conversion. Therefore, strengthening spatial governance through compact city approaches, mixed land use development, integrated transportation systems, and stricter land use control is necessary to support more sustainable urban development in Makassar City.